Uma análise discursivo-mediológica do sistema de publicações da Pedrazul, uma editora de clássicos inéditos no Brasil - Santos, Mariana da Silva Correa dos (Universidade Federal de São Carlos, 2025)
This work proposes to investigate the management of authorship in the editorial processes of Pedrazul's publishing system, from a discursive-mediological perspective based on studies of literary discourse (Maingueneau, 2006) and mediology (Debray, 1990; 2000), considering we noticed in Pedrazul's publishing system, an interesting system of authorship mediation. For that, we mobilized the editorial objects (Salgado, 2016; 2020; 2022) The Life of Charlotte Brontë (Gaskell, 2020), Pride and Prejudice (Austen, 2020), The Professor (Brontë, 2019) and Cecilia (Burney, 2022) published by Pedrazul through its three publishing seals, respectively the Official Website, the Readers' Club and Catarse. The analysis was based on the observation of the constitution of authorships in their paratopic node and on the “ways of doing” a media analysis proposed by Debray (2000), which occur at the levels: decentralizing, materializing and dynamizing. In the analysis, we made use of the scheme of “ideal types of independent publishers” proposed in a study of independent publishers in Brazil and Argentina (Muniz Jr., 2016), the concept of technemes in the analysis of editorial objects (Primo, 2019) and the notion of editorial paratexts (Genette, 2009). Overall, we conclude that Pedrazul is an independent publisher that promotes cultural diversity by publishing unpublished translations of foreign classics, especially english ones, into Brazilian Portuguese. Work that which, carried out by the publisher, mobilize discourses on classics and institutionalize associations between authors that were previously unknown to Brazilian readers, directing the circulation of books published by its three seals that project, at least, three profiles of readers of classics in Brazil.
A discursive-mediological analysis of the publication system of Pedrazul, a publisher of unpublished classics in Brazil
Keywords: Discurso literário; Mediologia; Gestão de autoria; Sistema de publicação; Pedrazul; Literary discourse; Mediology; Authorship management; Publishing system; LINGUISTICA, LETRAS E ARTES::LINGUISTICA